2020
DOI: 10.37231/mjis.2020.4.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Media as Platforms of Da’wah Among Muslim Converts in Borneo

Abstract: The study examined the use of media as tools of Muslim converts’ da’wah in Sabah, Sarawak and Brunei. There were two categories of media used in this study; social media (Facebook, YouTube, website, blog) and traditional media (television, radio, book, newspaper). The study interviewed 42 informants who lived in the city areas of Sabah, Sarawak and Brunei. The data obtained was arranged into themes and evaluated using descriptive and interpretive analysis approach. The study revealed that most informants parto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Such an act of transferring or seeking knowledge is also regarded as Muslims' obligation, hence the Ibadat or devotion to the Creator. This is also evident in the resurgence of Islam in the 21st century through various social media platforms and Islamic websites that are now easily accessible to many (Salim, 2020). For instance, these platforms provide users with information regarding Islam and simultaneously allow the users to engage interactively in seeking the required information (Khalid & Wan Razali, 2011).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Such an act of transferring or seeking knowledge is also regarded as Muslims' obligation, hence the Ibadat or devotion to the Creator. This is also evident in the resurgence of Islam in the 21st century through various social media platforms and Islamic websites that are now easily accessible to many (Salim, 2020). For instance, these platforms provide users with information regarding Islam and simultaneously allow the users to engage interactively in seeking the required information (Khalid & Wan Razali, 2011).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…A very popular example is the audiovisual translation of da'wah videos on YouTube. Da'wah refers to the act of spreading good deeds in Islam (Salim, 2020). Da'wah is an obligation of Muslims which covers simply asking fellow Muslims to do whatever Allah asks and to avoid what Allah hates or to teach about Islam to others.…”
Section: Fansubbingmentioning
confidence: 99%
“…Another study also examined the effectiveness of social media as the medium of da'wah among Muslim converts in Sabah and Sarawak, Malaysia (Salim, 2020). The study found that most respondents argued that every Muslim had a responsibility to disseminate da'wah based on their ability.…”
Section: Literature Review Social Media and Religionmentioning
confidence: 99%